Secure and reliable resource allocation in multi-function wireless systems - Lotfi, Ismail (Nanyang Technological University, 2023)
Multi-function wireless systems offer numerous benefits, such as efficient spectrum re-utilization and minimized hardware costs, by enabling multiple tasks to be performed simultaneously using the same spectrum or device. This has led to the widespread adoption of multi-function devices by various entities. However, these devices can be vulnerable to external threats, such as jammers or wardens, and can also be a source of attacks against the service provider with which they interact. Therefore, it is crucial to address the security and reliability challenges of multi-function wireless systems from different angles and perspectives. This thesis focuses on studying the security and reliability threats in multi-function wireless systems at three layers: the physical layer, networking layer, and application layer.